Digital Methods for Qualitative Research in the Social Sciences - (:unkn) unknown (My University, 2026)
European Science Foundation, EUROQUAL: Digital Methods for Qualitative Research in the Social Sciences, Cardiff University, 21st -25th May 2007 - Attended, sponsored by the ESFL